Functional outcome of minimal invasive anterior bridge plating for humerus shaft fractures - Pancholi, Priyank R.; Moradiya, Niravkumar Prabhudas; Nileshkumar, Khatri Chaitanya (International journal of health sciences, 2022)
Objectives: To study clinical & functional outcomes and complications in patients with humeral shaft fractures treated using anterior bridge plating. Materials and Methods: 25 patients with fractures of middle third humerus were treated with Minimum invasive Anterior Bridge plating in a case study at tertiary care hospital Surat. Both male and female patients above 20 years of age with closed and OG type I & II diaphyseal fractures of Humerus were included. Pathologic fracture, OG III fractures, Fractures in skeletally immature patients, Old neglected fractures, Those who Refused to provide informed consent and Fractures with neuromuscular disorders / neurovascular insufficiency were excluded. Functional outcome where analyzed by constant murley shoulder outcome score &Mayo elbow performance index. Results: The totals of twenty-five patients were included in the study. Out of total twenty-five patients 17 were males and 8 were females with the average age of 39 years. Right side fracture was found in 20 patients out of total 25. The average time for the surgery for the entire patient was 68 minutes.